Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kualitas Pendidikan - Hawana (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Leadership is the ability that exists in a leader in the form of certain traits, such as: Personality, Ability, and Capability. Leadership is a series of leader activities that cannot be separated from the position, style and behavior of the leader, as well as interactions between leaders, followers and situations. The education leader in this case is the principal as the person responsible for the implementation of education and teaching in educational institutions, must have the readiness and ability to arouse personal enthusiasm for work. This research was conducted to find the principal's leadership system in improving the quality of education in SDN No. 014727 Coal Cracker. This study uses a qualitative approach. Data collection is taken from interviews, observations and documentation which are all collected and analyzed to answer the research problems proposed by researchers in the focus of the study. The informants of this study are the Principal, Vice Principal in the field of curriculum, deputy headmaster in student affairs, deputy headmaster in facilities & infrastructure and teachers. The Principal tries to manage and oversee the administration of student, teaching, staffing, finance as well as facilities and infrastructure as well as possible. As a supervisor the school principal tries to help supervise his staff in developing programs, enhance teaching skills and skills, and conduct evaluations continuously.